2014
DOI: 10.5152/akd.2014.4918
|View full text |Cite
|
Sign up to set email alerts
|

No association between scar size and characteristics on T-wave alternans in post-myocardial infarction patients with relatively preserved ventricular function presented with nonsustained ventricular tachycardia

Abstract: Objective: Microvolt T-wave Alternans (TWA) is associated with abnormal repolarization and predicts arrhythmic mortality in patients with previous myocardial infarction (MI). Infarct tissue size and heterogeneity characterized by cardiac magnetic resonance (CMR) has been shown to be associated with arrhythmogenic substrates and sudden cardiac death. Although both delayed enhancement-CMR (de-CMR) and TWA are useful in risk stratification of post-MI patients with preserved left ventricular function, the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
(26 reference statements)
0
11
4
Order By: Relevance
“…Dinov et al showed a significant correlation between the surface of the endocardial scar and QRSf duration, while TWA levels were proportional to the size of the scar in simulation studies . In our study, none of the ECG, SA‐ECG, and TWA parameters were significantly correlated to the scar areas.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Dinov et al showed a significant correlation between the surface of the endocardial scar and QRSf duration, while TWA levels were proportional to the size of the scar in simulation studies . In our study, none of the ECG, SA‐ECG, and TWA parameters were significantly correlated to the scar areas.…”
Section: Discussioncontrasting
confidence: 58%
“…Twenty‐two patients were enrolled in this study. All patients had a history of previous MI 14 ± 9 years before, median 13 . Clinical characteristics are depicted in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several positive points in this manuscript (11). The aim of the study is very interesting and important from the clinical point of view.…”
mentioning
confidence: 98%
“…The Authors of the article entitled "No association between scar and characteristics on T-wave alternans in post-myocardial infarction patients with relatively preserved ventricular function presented with non-sustained ventricular tachycardia" published in this issue of Anatolian Journal of Cardiology tried to investigate important clinical issue concerning the relationship between electrical (TWA analyzed with the use of MMA method) and morphological (ECHO, CMR) results in a group of post-myocardial infarction patients (11). Of note, the link between electrical and morphological parameters of myocardium has been analyzed only in some experimental studies (12,13) and has not been clarified yet.…”
mentioning
confidence: 99%